Collaboration as a process and an outcome: Consumer experiences of collaborating with nurses in care planning in an acute inpatient mental health unit. (14th April 2018) - Reid, Rebecca; Escott, Phil; Isobel, Sophie
Abstract: This qualitative study explores inpatient mental health consumer perceptions of how collaborative care planning with mental health nurses impacts personal recovery. Semi‐structured interviews were conducted with consumers close to discharge from one unit in Sydney, Australia. The unit had been undertaking a collaborative care planning project which encouraged nurses to use care plan documentation to promote person‐centred and goal‐focussed interactions and the development of meaningful strategies to aid consumer recovery. The interviews explored consumer understandings of the collaborative care planning process, perceptions of the utility of the care plan document and the process of collaborating with the nurses, and their perception of the impact of collaboration on their recovery. Findings are presented under four organizing themes: the process of collaborating, the purpose of collaborating, the nurse as collaborator and the role of collaboration in wider care and recovery. Consumers highlighted the importance of the process of developing their care plan with a nurse as being as helpful for recovery as the goals and strategies themselves. The findings provide insights into consumers' experiences of care planning in an acute inpatient unit, the components of care that support recovery and highlight specific areas for mental health nursing practice improvement in collaboration.